Access to Physical Activity and Sport and the Effects of Isolation and Cordon Sanitaire During COVID-19 for People With Disabilities in Scotland and Canada - Kamyuka, Denise; Carlin, Liz; McPherson, Gayle; Misener, Laura (Frontiers in Sports and Active Living, 2020)
People with a disability are more at risk of experiencing inequalities in relation to sporting and physical activity opportunities, COVID-19 and the resulting restrictions stand to exacerbate these inequalities. This research directly contributes toward the World Health Organization, global research roadmap priority to explore “the impact of restrictive public health measures (e.g., quarantine, isolation, cordon sanitaire).” Social loneliness and social isolation have a significant impact on the health and wellbeing of individuals, therefore, it is imperative to gain an understanding of the effects of self-isolation and shielding during Covid-19 for people with disabilities to help those in policy and agency positions address these issues. This research utilized a qualitative approach, to speak with people with a disability, athletes and non-athletes and those in a position of management and policy making. Six online focus groups, with people participating in sport and physical activity, using live captioning, chat functions, and an online written discussion forum; through Project Echo website as part of a wider study on sport and accessibility were utilized. The study also drew on interviews and one of the focus groups was with senior policy makers and regional managers responsible for disability sport in Scotland.